Magma Plumbing During the 2014–2015 Eruption of Fogo (Cape Verde Islands) - Klügel, Andreas; Day, Simon; Schmid, Markus; Faria, Bruno (Frontiers in Earth Science, 2020)
Phenocrysts in volcanic rocks are recorders of magmatic processes that have occurred at depth before and during a volcanic eruption. Our petrological investigations of stratigraphically controlled tephrite and phonotephrite samples from the latest eruption of Fogo (Cape Verde Islands) aimed to reconstructing magma storage and transport. The dates of sample emplacement have been determined using satellite instrument - derived high resolution thermal infrared maps. All samples are strongly phyric and commonly contain complexly zoned clinopyroxene crystals and cumulate fragments. Clinopyroxenes from all samples exhibit 10-50 µm wide rim zones, inferred to have grown in a few days to weeks during the ongoing eruption as a consequence of H2O loss from the melt. Clinopyroxene-melt thermobarometry using tephrite groundmass compositions suggests that the rims formed at upper mantle pressures of around 600 MPa (21 km depth). This level is interpreted to reflect temporary reduction in magma ascent velocity by near-isobaric movement through a complex storage system. Previously, the tephrite magma had accumulated at a deeper level, possibly between 700 and 900 MPa as indicated by clinopyroxene cores (Mata et al., 2017). The cause for H2O loss initiating rim growth could be degassing after rise of the magma from the deeper level, or CO2 flushing by a carbonic fluid phase released at depth. Corresponding data from phonotephrites indicate last equilibration at around 440 MPa (16 km); the phonotephrite magma is inferred to be a residuum from an earlier magmatic event that was entrained by advancing tephrite. Microthermometry of CO2-dominated fluid inclusions in tephrite clinopyroxenes results in pressures of around 330 MPa (12 km), indicating another short pause in magma ascent in the lowermost crust. Rim zonations of olivine phenocrysts indicate that after leaving this final stalling zone, the magma ascended to the surface in less than half a day. In strong contrast to these petrological equilibration depths, seismic events precursory to the eruption were located at <5 km below sea level, with only two exceptions at 17 and 21 km depth consistent with our barometry. Our results enhance the understanding of this potentially dangerous volcano, which helps to interpret future pre-eruptive unrest.